Psychoanalysis and Affective Neuroscience. The Motivational/Emotional System of Aggression in Human Relations - Giacolini, Teodosio; Sabatello, Ugo (Frontiers in Psychology, 2019)
This paper highlights the evolutionary biological epistemology in Freud psychoanalytic theory. The concepts of aggressive and sexual drives are fulcrum of the psychoanalytic epistemological system, concerning the motivational/emotional roots of mental functioning. These biological roots of mental functioning, especially with regard to aggressive drive, have gradually faded away from psychoanalytic epistemology, as we show in the paper. Currently, however, Neurosciences, and in particular Affective Neuroscience (Panksepp 1998), can contribute to increase the knowledge of the biological roots of human mental functioning. The motivational/emotional systems studied by Affective Neuroscience can give a new epistemological foundation to the aggressive drive concept in psychoanalytic theory. Over the course of human evolution motivational/emotional systems have assumed the role of organizers of social relationships and also of mental functioning. In this regard, among the various types of aggression (ANGER in Panksepp taxonomy 1998), that we consider in our paper is inter-male aggression, also named Dominance motivational/emotional system, which regulates social interactions between sexually mature adults. This type of aggression acts in complementary connection with FEAR motivational/emotional system, that regulate Submissive behaviour and Social defeat, the latter one of the more important stressors. The interaction between aggressiion and FEAR motivational/emotional systems gives rise to Agonistic behaviour or Dominance/Submission motivational/emotional system, as we propose in our paper. There is now a large literature that identifies in the dynamic of Agonistic behaviour one of the main factors of mental illness. When social interactions activate the Agonistic behavior, the subject can perceive himself as "destined to victory" or "destined to defeat", activating either behaviours and emotions connected to the Involuntary Defeat Strategy or Involuntary Dominant Strategy, that we can find in many types of mental disorders, e.g. mood disorders or anxiety disorders.